Quality of life of elderly stroke patients and their caregivers - Parová, Valéria; Sováriová Soósová, Mária; Suchanová, Renáta (Magyar Gerontológia, 2022)
Stroke represents a major societal representation as well as economic problem in an individual's life. The question arises in connection with the life of the patient oneself as well as in one’s whole family. Stroke is one of the most common diseases affecting people at an old age.